Isolation of a Psychrotolerant and Uv-C-Resistant Bacterium from Elephant Island, Antarctica with a Highly Thermoactive and Thermostable Catalase - Blamey-Alegria, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Microorganisms present in Antarctica have to deal not only with cold temperatures but also with other environmental conditions, such as high UV radiation, that trigger the generation of reactive oxygen species. Therefore, Antarctic microorganisms must have an important antioxidant defense system to prevent oxidative damage. One of these defenses are antioxidant enzymes, such as catalase, which is involved in the detoxification of hydrogen peroxide produced under oxidative conditions. Here, we reported the isolation and partial characterization of an Antarctic bacterium belonging to the Serratia genus that was resistant to UV-C radiation and well-adapted to cold temperatures. This microorganism, denominated strain I1P, was efficient at decreasing reactive oxygen species levels produced after UV-C irradiation. Genomic and activity assays suggested that the enzymatic antioxidant defense mechanisms of strain I1P, especially its catalase enzyme, may confer UV resistance. This catalase was active in a wide range of temperatures (20–70° C), showing optimal activity at 50° C (at pH 7.0), a remarkable finding considering its psychrotolerant origin. In addition, this enzyme was thermostable, retaining around 60% of its activity after 6 h of incubation at 50° C. The antioxidant defense systems of strain I1P, including its surprisingly thermoactive and thermostable catalase enzyme, make this microorganism a good source of biocompounds with potential biotechnological applications. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.